Merchandising metrics and your selection criteria - Miranda Sánchez, Erick (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.560, 2021)
This article analyzes the merchandising metrics, because companies see the need to use efficient tools that allow them to measure the productivity of the point of sale, based on different analysis indicators considered in the relationship to sales, the external layout of the store and the organization of the products handled within the shelf. For the following research, an exploratory methodology was considered, as well as a bibliographic method based on books and virtual articles of different authors related to the research topic. Among the main results, it is worth mentioning that, depending on the user’s needs, there are several metrics that are aimed at a specific objective, which help in the decision making process. In conclusion, purchase decisions are influenced by different factors and these must be measured to know the impact it has.